Home Video Curriculum for Basic Surgical Skills - Hueylan Chern; Leslie Sheu; Patricia O'Sullivan; Edward Kim (Association of American Medical Colleges, 2014)
Abstract This resource is a video curriculum designed to help prepare first-year surgical residents for knot-tying and suturing in the operating room. A series of exercises is designed to simulate scenarios in the operating room, minimize contextual variations, and improve performance. The low cost for setting up and running the models makes the curriculum applicable to most training programs. In the beginning of the year, each intern is given a starter kit including basic surgical instruments, knot tying boards, cameras, and tripods. The curriculum includes five assignments and the specific tasks and set-up are described and demonstrated in the resource files. Tasks are assigned biweekly, beginning with home video assignment one and ending with home video assignment five. Residents are given a 2-week period to complete each assignment. They are instructed to practice at home until they feel that their performance is ready for submission and review. Previous surveys showed that most first-year students practiced one to ten times before recording their final product. It is important that residents set up their recording so that they replicate the instruction videos with hands/forearms in view. The duplicated vantage point provides direct comparison for reviewers to more easily comment on the kinesthetic of each performance. We found it helpful to have a resident-to-faculty ratio of two or three-to-one, as each assignment can contain up to seven video clips to review. Each faculty member devoted 1 to 1.5 hours every 2 weeks to review the videos.